PENINGKATAN PRESTASI BELAJAR PENDIDIKAN JASMANI MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW (Studi Pada Siswa Kelas X SMK Al Ikhlash Panceng Gresik) - Qomarrullah, Rif’iy (Ordik, 2013)
A numbers of researches have been many times conducted in relation to the cooperative instruction with the jigsaw base. This research was conducted by expanding the instruction instrument characterized by the jigsaw type cooperative instruction model as one of alternatives in coping with the physical educational instruction problem. The lack of communication could have effect on the student activities and the learning achievements of physical education in the school, and then it could be formulate the problems as follows: what are the student responses to the application of jigsaw type cooperative instruction instrument?, what are the student learning outcomes in the form of product and process in the jigsaw type cooperative instruction? The specific purposes of this research was to describe the student responses to the application of jigsaw type cooperative instruction instrument, describe the student learning outcomes in the form of product and process in the jigsaw type cooperative instruction. In this research used the classroom action research (CAR) design. Subjects in this research were the students of class XB at the Al Ikhlas Vocational Senior High School of Panceng Gresik amounted to 31 students (17 male and 14 female). Data collection technique in this research used the observation, questionnaire, field record, test and, documentation methods. The fundamental material used in this research was the squat style long jump. The times used were 6 times of encounters. Results are as follows: 1.) Produced FCE recapitulation learning success rate indicates the long jump squat style categories very good results, it shows that students are very pleased with the use type of jigsaw cooperative learning model. 2.) Percentage of observation and mastery learning show student learning outcomes of learning processes and products in the long jump squat style good category. Therefore, the type of jigsaw cooperative learning can help teachers of physical education in the learning process.  The writer hope that this research can be made as reference by the related parties such as teachers, parents, and the further researchers in developing the ability to socially interact with the surrounding environment and can improve the student activities and student learning outcomes in the school by means of jigsaw type cooperative instruction.   Kata kunci: kooperatif tipe jigsaw, pendidikan jasmani, prestasi belajar.